Factors contributing to the acceptance of social media as a platform among student entrepreneurs: A review - Noorlisa Maria A. Hamid Shokery; Noorshella Che Nawi; Noorul Azwin Md Nasir; Abdullah Al Mamun (Mediterranean Center of Social and Educational Research, 2016)
Social media has become a major development in e-commerce and a platform for student entrepreneurs, not only to sell goods and services but also to interact and connect with customers. The purpose of this paper is to identify the factors contributing to the acceptance of social media as a platform among student entrepreneurs in Malaysia. Earlier studies on social media have mostly focused on how students use social media for academic purposes. However, limited research has been done on how students or young entrepreneurs use social media as a platform to operate their business. A modified ‘Unified Theory of Acceptance and Use of Technology’ (UTAUT) is used as the theoretical framework to examine the level of acceptance of social media as a platform among student entrepreneurs. The key factors that contribute to the acceptance of social media as a business platform are performance expectancy, effort expectancy, social influence, facilitating condition, and perceived enjoyment.